The prevalence and severity of injuries in a youth basketball academy with a differential learning-based strength and conditioning program: Two-season prospective observational cohort study - Arede, J.; Zhou, R.; Shang, X.; Leite, N.; Schöllhorn, W. (International Journal of Sports Science & Coaching, 2025)
This study aimed to evaluate the effectiveness of a DL-based strength and conditioning programme in reducing the incidence and severity of injuries among adolescent basketball players and to explore its underlying mechanisms. This prospective observational cohort design involved 64 adolescent basketball players (43 males, 21 females; aged 11-17 years), who were monitored over two consecutive competitive seasons (a total of 20 months). Injury data were collected using a customised questionnaire, including type, location, severity, and occurrence. Participants were divided into two groups based on training frequency: once and twice-weekly training groups. Fifty-six injury incidents were recorded over the two seasons. Lower extremity injuries accounted for 78.6% of all cases, with ankle sprains being the most common (41.1%), followed by knee injuries (21.4%). Acute injuries constituted 89.3% of all cases, with 58.0% resulting from direct contact. The ratio of injuries per athlete decreased from 0.53 injuries per athlete in the first season to 0.34 injuries per athlete in the second season. No statistically significant differences were found between the training groups regarding the number or severity of injuries. Kaplan-Meier survival analysis also showed no significant differences in survival probability between groups, despite a slightly higher restricted mean survival in the twice-weekly training group. This decline suggests that the DL-based training programme may have helped reduce injury risk among adolescent basketball players, enhancing neuromuscular control and motor adaptability. Future research should further investigate the long-term effects of DL and its broader application across different sports and populations.